A Meningkatkan Pembelajaran PAI dengan Analisis Nilai Ujian: Identifikasi dan Intervensi Siswa Berbasis Distribusi Nilai - Akbar Waliyuddin Pakpahan, Akbar; Anshori, Ari (Edusifa: Jurnal Pendidikan Islam, 2024)
This study aims to improve the effectiveness of Islamic Religious Education (PAI) learning through analysis of the distribution of practical and written exam scores, focusing on identifying students who need intervention and developing more effective learning strategies. Data on practice and written test scores from 21 students were analyzed to understand the distribution and variation of grades. The results of the analysis showed that the average score of the practical exam was 84.10, while the score of the written exam was 82.19, with a range of scores between 74 to 92. Higher standard deviations in written exam scores indicate greater variation in student comprehension. These findings highlight the importance of paying special attention to students whose test scores are below the median, as well as designing learning interventions that suit their needs. Teachers can use value distribution data to develop more interactive and individual needs-based learning strategies for students, as well as allocate additional resources to strengthen understanding on challenging topics. As such, the study provides practical insights into how value distribution analysis can be used to improve the quality of PAI learning and ensure every student gets the support needed to reach their academic potential.